PENGARUH PHYSICAL EVIDENCE DAN PROCESS TERHADAP LOYALITAS ANGGOTA PADA KOPERASI PONDOK PESANTREN BAETUR RAHMAN KABUPATEN BOGOR - Ahmad Fauzi; Lucky Hikmat Maulana (Jurnal Visionida, 2015)
This study aims to determine the responses of members and the influence of physical evidence and process for loyalty members in the Koperasi Pondok Pesantren Baetur Rahman Kabupaten Bogor and the object of this research is a member of the Cooperative of 100 members sampled. The method used is verification, Validity, Reliability Test, using multiple regression analysts, analysis of correlation coefficients and coefficients of determination (R2) were subsequently tested by the F test and t test. Based on the recapitulation of respondents to the physical evidence is quite agree, disagree and loyalty process that members do not agree. The multiple regression analysis of the F test states that the simultaneous physical evidence and process and partial t test physical evidence and process real and positive impact on loyalty members of Koperasi Pondok Pesantren Baetur Rahman Kabupaten Bogor, of the product moment correlation analysis states that the existence of a strong relationship between physical evidence, process with loyalty members, determination of the results of the analysis states that 60.2% of the contribution of physical evidence and process the loyalty of members and of the results of the t test states that the physical evidence and partially process significantly affect the loyalty members of Koperasi Pondok Pesantren Baetur Rahman Kabupaten Bogor.Keywords: Physical evidence, process, loyalty members